IMPLEMENTASI REKRUTMEN GURU HONORER DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SMA NEGERI 1 TUHEMBERUA - Zai, Nirmala; Zega, Yamolala; Hulu, Fatolosa; Telaumbanua, Eliagus (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to describe the recruitment process of honorary teachers at SMA Negeri 1 Tuhemberua and to analyze the impact of student learning outcomes on the recruitment of honorary teachers at SMA Negeri 1 Tuhemberua. This study uses a qualitative method with five informant. The data collection techniques used are observation, interviews and documentation. Researchers use data analysis techniques including data reduction, data presentation and drawing conclusions. The results of the study show that the recruitment process for honorary teachers at SMA Negeri 1 Tuhemberua is guided by law Number 14 of 2005 concerning Teachers and Lecturers Article 9 which states that academic qualifications as referred to in Article 8 are obtained through higher education, undergraduate programs or diploma four programs, prospective honorary teachers submit applications or letters addressed to the principal. The next step is for the application acceptance committee to verify the administrative documents. If the documents meet the administrative honorary teachers will be contacted for an interview. Once the prospective honorary teachers pass the interview, they will be assigned to teach in the classroom. The impact of student learning outcomes at SMA Negeri 1 Tuhemberua after the recruitment of honorary teachers has seen a significant increase in student learning outcomes, as evidenced by the large number of students in the class who are more enthusiastic and active in class. Students at SMA Negeri 1 Tuhemberua have participated in numerous academic activities in the National Science Olympiad (OSN) competitions in Geography, Astronomy, Mathematics, Chemistry and Physics. These students have competed at the Regency and Provincial levels. In addition to academic activities, students of SMA Negeri 1 Tuhemberua are able to participate in no-academic activities such as football, volleyball, martial arts, arts and cultural arts studios, FLS2N and two students of SMA Negeri 1 Tuhemberua won 1st and 3rd place in the 2024 North Nias Regency Tourism Princess event at the sub-district, district and provincial in North Sumatra. This means that the quality of education at SMA Negeri 1 Tuhemberua is very good, this cannot be separated from the quality of the teachers themselves.Keywords: Implementatio, Honorary Teachers, Quality of Education.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan proses rekrutmen guru honorer di SMA Negeri 1 Tuhemberua dan untuk menganalisis dampak hasil belajar siswa terhadap perekrutan guru honor di SMA Negeri 1 Tuhemberua. Penelitian ini menggunakan metode kualitatif dengan jumlah informan lima orang. Tekinik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Peneliti menggunakan teknik analisis data antara lain reduksi data, penyajian data dan penarikan kesimpulan.Hasil penelitian menunjukkan bahwa proses perekrutan guru honorer di SMA Negeri 1 Tuhemberua mengikuti peraturan komite sekolah SMA Negeri 1 Tuhemberua dengan berpedoman pada Undang-Undang Nomor 14 Tahun 2005 tentang Guru dan Dosen Pasal 9 yang berbunyi kualifikasi akademik sebagaimana dimaksud dalam Pasal 8 diperoleh melalui pendidikan tinggi program sarjana atau program diploma empat, Para calon guru honor menyerahkan permohonan atau surat yang ditujukan kepada Kepala Sekolah. Dan langkah selanjutnya oleh Panitia penerimaan berkas lamaran akan melakukan verifikasi terhadap berkas administrasi. Apabila berkas memenuhi syarat administrasi maka calon guru honor dihubungi untuk mengikuti tahapan seleksi wawancara. Ketika calon guru honor dinyatakan lulus wawancara maka akan diberikan tugas mengajar dikelas. Dampak hasil belajar siswa di SMA Negeri 1 Tuhemberua setelah perekrutan guru honor terjadi peningkatan hasil belajar siswa signifikan terbukti dengan banyaknya siswa didalam kelas lebih semangat dan giat dalam belajar. Siswa di SMA Negeri 1 Tuhemberua telah banyak mengikuti kegiatan akademik dalam perlombaan Oliampiade Sains Nasional (OSN) bidang mata pelajaran Geografi, Astronomi, Matematika, Kimia dan Fisika. Para siswa yang mengikuti perlombaan tersebut mampu berkompetisi ditingkat Kabupaten dan tingkat Propinsi. Selain kegiatan akademik, para siswa SMA Negeri 1 Tuhemberua mampu mengikuti kegiatan non akademik seperti kegiatan olahraga sepak bola, volly ball, pencak silat, seni dan sanggar budaya, FLS2N dan dua siswa SMA Negeri 1 Tuhemberua mendapat juara 1 dan 3 pada kegiatan Putri Pariwisata Kabupaten Nias Utara tahun 2024 ditingkat Kecamatan, Kabupaten dan Propinsi Sumatera Utara. Artinya, bahwa kualitas pendidikan di SMA Negeri 1 Tuhemberua sangat baik, hal tersebut tidak terlepas dari kualitas guru itu sendiri.Kata kunci: Implementasi, Guru Honor, Kualitas Pendidikan